SN 2021zny: an early flux excess combined with late-time oxygen emission suggests a double white dwarf merger event. Issue 1 (27th February 2023) - Dimitriadis, Georgios; Maguire, Kate; Karambelkar, Viraj R; Lebron, Ryan J; Liu (刘 畅), Chang; Kozyreva, Alexandra; Miller, Adam A; Ridden-Harper, Ryan; Anderson, Joseph P; Chen, Ting-Wan; Coughlin, Michael; Valle, Massimo Della; et al.
ABSTRACT: We present a photometric and spectroscopic analysis of the ultraluminous and slowly evolving 03fg-like Type Ia SN 2021zny. Our observational campaign starts from ∼5.3 h after explosion (making SN 2021zny one of the earliest observed members of its class), with dense multiwavelength coverage from a variety of ground- and space-based telescopes, and is concluded with a nebular spectrum ∼10 months after peak brightness. SN 2021zny displayed several characteristics of its class, such as the peak brightness ( MB  = −19.95 mag), the slow decline (Δ m 15 ( B ) = 0.62 mag), the blue early-time colours, the low ejecta velocities, and the presence of significant unburned material above the photosphere. However, a flux excess for the first ∼1.5 d after explosion is observed in four photometric bands, making SN 2021zny the third 03fg-like event with this distinct behaviour, while its +313 d spectrum shows prominent [O i ] lines, a very unusual characteristic of thermonuclear SNe. The early flux excess can be explained as the outcome of the interaction of the ejecta with $\sim 0.04\, \mathrm{M_{\odot }}$ of H/He-poor circumstellar material at a distance of ∼10 12 cm, while the low ionization state of the late-time spectrum reveals low abundances of stable iron-peak elements. All our observations are in accordance with a progenitor system of two carbon/oxygen white dwarfs that undergo a merger event, with the disrupted white dwarf ejecting carbon-rich circumstellar material prior to the primary white dwarf detonation.